KORELASI ANTARA MINAT DENGAN PRESTASI BELAJAR BAHASA JERMAN MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JERMAN FAKULTAS BAHASA DAN SASTRA UNIVERSITAS NEGERI MAKASSAR - Misnawaty Usman; Burhanuddin Burhanuddin; Nurming Saleh (Universitas Negeri Makassar, 2022)
This research is ex post facto correlational nature that aims to determine how the correlation between interest in learning the German language learning achievements of students of the German language education FBS-UNM. The population in this study were students of the even semester academic year 2020-2021German language education study pogram FBS-UNM totaled 42 students .Its well as a sample in this study (total sample). Data collection techniques used in this study is Lickert Scale and tests. Data were analyzed using correlation techniques